Correlation of FFR measured after DES implantation with clinical parameters and long-term clinical outcome. (3rd October 2022) - Csanadi, B; Fulop, G; Szoke, S; Szonyi, T; Dekany, G; Pinter, T; Takacs, P; Abdelkrim, A; Beres, A; Fontos, G; Andreka, P; Nyolczas, N; et al.
Abstract: Introduction: The role of fractional flow reserve (FFR) measured directly after drug eluting stent (DES) implantation (post-PCI FFR) is not clear in predicting major adverse cardiac events (MACE), and it is not known which clinical parameters affect post-PCI FFR. Aim: We aimed to clarify the relationship between post-PCI FFR and clinical parameters, post-PCI FFR and long-term MACE and determine the best post-PCI FFR cut-off in MACE prediction. Method: Patients who underwent post-PCI (DES) FFR measurement at our center between March 2009 and January 2021 were included. We examined the relationship between post-PCI FFR and gender, age, hypertension, diabetes mellitus, hyperlipidemia, indication (acute (ACS) vs. chronic coronary syndrome (CCS)), stent diameter, in-stent restenosis vs de novo lesion category, proximal vs. non-proximal lesion location, LAD (vs. non-LAD) location, and pre-PCI FFR. We sought to determine the correlation between post-PCI FFR and target vessel-related MACE (cardiovascular death (CVD), non-fatal myocardial infarction (MI), recurrent revascularization (TVR)). Optimal cut-off was determined by ROC curves. Results: Post-PCI FFR measurement was performed in 500 coronary arteries of 434 patients. LAD location (0.86 vs. non-LAD 0.91, p<0.001), male gender (0.87 vs. 0.89, p=0.001), younger age (p=0.0215), smaller stent diameter (p=0.0028) and lower pre-PCI FFR (p=0.0006) proved to be independent predictors of lower post-PCI FFR, no other parameter showed a significant correlation with post-PCI FFR. During a median follow-up of 37 months, 24 CVD, 15 MI and 47 TVR occurred. Follow-up was complete in 96.2% of patients. There was a significant inverse correlation between post-PCI FFR and MACE (p<0.001). Diabetes mellitus (p=0.0024) and in-stent restenosis (0.0356) were also independent predictors of MACE. The best post-PCI FFR cut-off for the total patient population, LAD and non-LAD lesions were 0.83 (p<0.0001), 0.83 (p<0.0001), and 0.88 (p=0.0091), respectively. Conclusion: LAD location, male gender, younger age, smaller stent diameter and lower pre-PCI FFR value result in lower post-PCI FFR. There is no significant difference between post-PCI FFR measured in ACS vs. CCS. FFR measured after PCI, diabetes mellitus and in-stent restenosis are significant predictors of MACE-free long-term survival. The best post-PCI FFR cut-off to predict MACE was 0.83 for the whole patient population and for LAD and 0.88 for non-LAD lesions. Funding Acknowledgement: Type of funding sources: None.